Могильник черняхівської культури біля с. Легедзине на Черкащині. Розкопки 2008—2009 рр. - Магомедов, Б.В.; Діденко, С.В. (Археологічні дослідження в Україні, 2010)
During 2008 and 2009 seasons 26 graves (15 cremations and 11 inhumations) of Chernyakhivska culture were discovered at the burial ground near Lehedzyne village in Cherkasy Oblast. In tombs and in the cultural layer there were found mostly local wheel-made pottery, one handmade and one imported dishes, and also combs, fibulae, buckles, tweezers, knives, beads, and pendants made of bronze, iron, silver, gold and leather. The materials are dated by the 4th c.